Adiposity Epidemiology and Treatment Modalities - Oxholm Gordeladze, Jan (IntechOpen, 2017)
This book is the first in a series of two, featuring the Adiposity - Epidemiology and Treatment Modalities, serving as a summary of the traditional views on how the organ systems are affected when higher organs start to suffer from enhanced body weight, where most of this additional weight consists of white adipose tissue (WAT). The understanding of the "epidemiology" of obesity will consequently enable clinicians and researchers to better understand the untoward "trends" of "metabolic aberrations" from a well-organized and health-bringing homeostasis, with fully responding WAT and BAT, thus enabling a balance between fat-producing and fat-metabolizing tissues for the benefit of the various organ systems taking care of the fat and carbohydrate metabolism, normally yielding a balanced energy turnover, ensuring "healthy" cell phenotypes, which optimally coordinate the energy metabolism in a well-functioning organism throughout a lifetime.